Implementasi Strategi Pemasaran Berbasis Internet Marketing Untuk Meningkatkan Pendapatan Pada LAZNAS Nurul Hayat Surrabaya - Khoirudin, Mohamad Hamam; Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2020)
The use of internet marketing such as marketing through social media, websites and digital channel are commonly used. Especially in marketing strategies using an internet marketing. This study aims to determine the implementation of internet marketing-based marketing strategies to revenue at LAZNAS Nurul Hayat Surabaya. This research uses descriptive qualitative research methods and conducts an in-depth interview. The results of this study indicate that the implementation of internet marketing-based marketing strategies is influential on income in a company or institution but still on a constraints on the quality of existing human resources.